POTENTIAL OF ACTIVE COMPOUNDS LEAVES OF MANGO PARASITE (Dendrophthoe pentandra (L). Miq) AS ANTIFUNGAL - M.Ridha Mauludi; Harry Widjajanti; Elisa Nurnawati (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2022)
Infection is a disease that is easily found in tropical areas such as Indonesia. The causes of infection that are easily found include infections due to fungi. One of the fungi that causes many infections is the Candida fungus. Tropical drugs commonly used to treat cutaneous candidiasis include nystatin, clotrimazole, miconazole, ketoconazole and other azoles. However, antifungal drugs have limitations, such as severe side effects, poor penetration into certain tissues, and the emergence of resistance. To overcome the negative effects caused by these synthetic antifungal drugs, it is necessary to explore natural antifungal drugs. One of the plants that has the potential as a medicinal plant is the mango parasite plant (Dendrophthoe pentandra (L.) Miq) which is a parasitic plant that attaches to the host which has the potential as herbal medicine. Research on the potential of active compounds in the leaves of mango parasite (Dendrophthoe pentandra (L). Miq) as antifungals has been carried out from November 2020 to June 2021 at the Genetics and Biotechnology Laboratory, Biology Department, FMIPA Sriwijaya University. The purpose of this study was to obtain fractions that had antifungal activity, to obtain isolates that had antifungal activity, what active compounds were present in the leaves of the mango parasite as antifungal, and to determine the minimum inhibitory concentration of the fungus Candida albicans. Based on research that has been carried out with methanol, n-hexane and ethyl acetate extracts that are active as antifungals, namely n-hexane and ethyl acetate extracts with an n-hexane inhibition zone diameter of 12 mm while ethyl acetate is 10 mm. Then purification of the n-hexane and ethyl acetate fractions was carried out using gravity column chromatography and the n-hexane fraction obtained two pure compounds that were active as antifungals, namely isolate N-1 with a diameter of 12 mm and N-4 with a diameter of 10 mm. Two pure acetate fractions were obtained which were active as antifungals, namely isolates E-1 with a diameter of 10 mm and E 5 with a diameter of 12 mm. Furthermore, the results of the eluate were tested by MIC and thin layer chromatography (TLC). The MIC results on isolates N-1, N-4, and E-1 were able to inhibit at a concentration of 500 ppm and were classified as strong. Meanwhile, isolate E-5 was able to inhibit at a concentration of 1000 ppm which was classified as moderate. The TLC results showed color spots on isolate N-1 which were blue, namely terpenoids, while in isolate N-4 which was orange in color were alkaloids, while in isolate E-1, the color was phenolic yellow, while in isolate E-5, which was purple, it was group terpenoids. The results of the bioautography of isolate N-1 with R¦ value: 0.9, isolate N-4 with R¦: 0.6, isolate E-1 with R¦ value: 0.8, and isolate E-5 with R¦ value: 0,9.